EVALUATION OF THE EFFICACY OF ANGIOTENSIN II RECEPTOR ANTAGONISTS (LOSARTAN) ON THE STATE OF CENTRAL HEMODYNAMICS IN PATIENTS WITH THYROTOXICOSIS SYNDROME (Spectrum Journal of Innovation, Reforms and Development, 2026)
Purpose of the study– to study the effectiveness of the drug losartan on the state of central hemodynamics in patients with thyrotoxicosis syndrome. Material and methods of research. Clinical data collection was carried out at the City Clinical Hospital No. 1 in Andijan 63 people were examined, including 47 women, 16 men, average age49.2±1.62years (for women -47±1.76years, for men -42±2.6years). Patients with thyrotoxicosis syndrome, depending on the disease, were divided into the following 5 groups: patients with diffuse toxic goiter 50% - DTG- (32 people), multinodular goiter - MUZ-11.6% (7 people), autoimmune thyroiditis - AIT-16.7% (11 people), thyrotoxic adenoma - TA-6.7% (4 people) and mixed toxic goiter - MS-15% (9 people). Research methods – general clinical, biochemical (bilirubin, direct, indirect, ALT, AST, PTI, coagulogram, CRP), hormonal (TSH, free thyroxine, antibodies to thyroid peroxidase, to thyroglobulin and thyrocyte receptors, prolactin in the blood),anthropometric calculations (height (cm), weight (kg), BMI (kg/m2), waist circumference, waist circumference) and instrumental: ECG, echo-ECG, ultrasound of the thyroid gland, internal organs, chest X-ray Research results.The study revealed significant changes that suggest that losartan therapy reverses left ventricular hypertrophy (LVH) and improves its structural characteristics in patients with hyperthyroidism syndrome. Left atrial (LA) dilation was found to be a precursor to LVH. Combined use of losartan demonstrated the ability to significantly reduce the size of the left atrium, which was enlarged in most patients examined. Consequently, the observed statistically significant reduction in LA size from 4.42 ± 0.08 to 3.81 ± 0.09 cm (p < 0.05) can be interpreted as a positive effect of losartan therapy. Conclusions.The inclusion of losartan, an angiotensin II receptor blocker, in combination therapy including beta-blockers and antithyroid drugs, against the background of achieved compensation of thyrotoxicosis, led to regression of left ventricular hypertrophy, restoration of sinus rhythm in 43% of patients and a statistically significant improvement in blood pressure.